2016
DOI: 10.7861/clinmedicine.16-4-315
|View full text |Cite
|
Sign up to set email alerts
|

Options for taking time out of specialty training

Abstract: Trainees in higher specialty training programmes may have the option to take time out of their training programme to enhance or broaden their skills and perhaps develop a sub-specialty interest. Traditionally, out of programme experience has been mostly taken by clinical academic trainees in order to undertake a higher research degree. However, there are a growing number of other ways to usefully spend time out of programme. This article is intended to highlight the range of opportunities and explain the moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Participants embarked upon a range of formal qualifications during their time out, ranging from specialty membership exams to a PhD. A Higher Education Academy 25 systematic review identified that career progression should involve enhancing and empowering the learner to take control of their own career. Our participants who re-entered UK training returned with broader portfolios of experience, which enhanced competitiveness in a way similar to those who take time out at later stages during specialty training programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Participants embarked upon a range of formal qualifications during their time out, ranging from specialty membership exams to a PhD. A Higher Education Academy 25 systematic review identified that career progression should involve enhancing and empowering the learner to take control of their own career. Our participants who re-entered UK training returned with broader portfolios of experience, which enhanced competitiveness in a way similar to those who take time out at later stages during specialty training programmes.…”
Section: Discussionmentioning
confidence: 99%